2006
DOI: 10.1111/j.1462-5822.2006.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF-mediated inhibition of JNK is a key mechanism for Lactobacillus rhamnosus-induced suppression of TNF production in macrophages

Abstract: SummaryLactobacillus rhamnosus is a human commensal with known immunomodulatory properties. To date the mechanism of these immunomodulatory effects is not well understood. To unravel the immunomodulatory signalling mechanism, we investigated the effects of two strains of L. rhamnosus , L. rhamnosus GG and GR-1, in modulating production of tumour necrosis factor-a (TNF) in human monocytic cell line THP-1 and mouse macrophages. Live L. rhamnosus GG and GR-1 or their spent culture supernatant induced minuscule am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 78 publications
(120 reference statements)
8
102
0
1
Order By: Relevance
“…54 While the mechanism governing G-CSF-mediated cytokine inhibition remains unclear, recent studies have suggested a role for STAT3. 58,59 Collectively, these data suggest an important role for G-CSF in the down-regulation of the local inflammatory response.…”
Section: Discussionmentioning
confidence: 81%
“…54 While the mechanism governing G-CSF-mediated cytokine inhibition remains unclear, recent studies have suggested a role for STAT3. 58,59 Collectively, these data suggest an important role for G-CSF in the down-regulation of the local inflammatory response.…”
Section: Discussionmentioning
confidence: 81%
“…LR has been shown to be capable of inhibiting the onset of experimental colitis in transgenic IL-10-deficient mice (21) and has further been shown to reduce intestinal permeability to macromolecules (20). Probiotics are capable of inhibiting TNF production in activated macrophages (16,27). A recent publication by Lin et al (18) showed that LR suppressed the production of TNF from lipopolysaccharide-activated human monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Each blasticidin resistance clone was cultured for 2 wk and tested for TNF-␣ production in response to LPS (1 g/ml). TNF-␣ bioassay was performed as previously described (26). To rescue retroviral insertion-induced mutations, CTSB mut , a partial mRNA sequence of the fused gene product, was transfected with a retroviral vector expressing Cre (pBaBe-Cre) and puromycin resistance gene.…”
Section: Mutagenesis With Retrovirus Screening For Defects In Tnf-␣mentioning
confidence: 99%